2014
DOI: 10.1128/iai.02111-14
|View full text |Cite
|
Sign up to set email alerts
|

The AgrD N-Terminal Leader Peptide of Staphylococcus aureus Has Cytolytic and Amyloidogenic Properties

Abstract: Staphylococcus aureus virulence is coordinated through the Agr quorum-sensing system to produce an array of secreted molecules. One important class of secreted virulence factors is the phenol-soluble modulins (PSMs). PSMs are small-peptide toxins that have recently been characterized for their roles in infection, biofilm development, and subversion of the host immune system. In this work, we demonstrate that the signal peptide of the S. aureus quorum-sensing signal, AgrD, shares structural and functional simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 66 publications
2
40
0
Order By: Relevance
“…PSM peptides were synthesized by LifeTein (South Plainfield, NJ) and assayed to be Ͼ90% pure by high-performance liquid chromatography (HPLC). Synthetic peptides were prepared as previously described (33). Briefly, the peptides were resuspended in hexafluoroisopropanol (HFIP), and 0.5 mg was aliquoted into microcentrifuge tubes.…”
Section: Methodsmentioning
confidence: 99%
“…PSM peptides were synthesized by LifeTein (South Plainfield, NJ) and assayed to be Ͼ90% pure by high-performance liquid chromatography (HPLC). Synthetic peptides were prepared as previously described (33). Briefly, the peptides were resuspended in hexafluoroisopropanol (HFIP), and 0.5 mg was aliquoted into microcentrifuge tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, other FPR agonists, such as phenol-soluble modulin peptide toxins (15), amyloid-␤(1-42) (8), or PAR (57), may also fit into this scheme. For example, a recent study demonstrated that the signal peptide of the Staphylococcus aureus quorum-sensing signal, AgrD, shares clear structural and functional similarities with the phenol-soluble modulin family (50). The fact that critical agonist features as described here extend to a number of distinct FPR agonists suggests that our results should prove useful in future developments, such as the identification of the FPR ligand binding site and the discovery of subtype-selective FPR antagonists.…”
Section: Discussionmentioning
confidence: 68%
“…3G), predicting that rev-W-peptide should function as a potent FPR activator. When we tested this, we found indeed nearly identical EC 50 values for this peptide on hFPR1 and mFpr1 (Fig. 3H).…”
Section: Structurally Dissimilar Peptide Agonists Imply a Conserved Fmentioning
confidence: 59%
See 1 more Smart Citation
“…Thus, PSMs are bifunctional proteins that may be stored as inert fibrils in a sessile biofilm until conditions arise that favor their dissociation to promote biofilm disassembly and virulence (47). Recent evidence suggests that PSM aggregation can be accelerated by the presence of trace amounts of AgrD, the signal peptide of the S. aureus quorum-sensing system, since AgrD would self-aggregate and act as seeds, allowing the incorporation of PSMs into the growing aggregate (53).…”
Section: Amyloid Structures With Dedicated Fiber Assembly Machinerymentioning
confidence: 99%